Modulation of the NF-κB Activation Pathway by Phycocyanobilin from Spirulina platensis: An in Silico Study - Iswanti, Febriana Catur; Purba, Hastuti Handayani S; Prijanti, Ani Retno; Fadilah, Fadilah; Herlina, Linda; Paramita, Reni (UI Scholars Hub, 2022)
Several studies have predicted the molecular interactions of the active ingredient of Spirulina platensis as an anti-inflammatory compound. However, these interaction studies did not review the modulation of the NF-κB activation pathway, which involves various factors. This study demonstrated the potential of the bioactive compounds of S. platensis for modulating immune function by reducing inflammation through the inhibition of the NF-κB activation pathway. Phycocyanobilin was predicted to have good potential for molecular docking with multisubunit IκB kinase (IKK)1/IKKA, IKK2/IKKB, NF-κB-inducing kinase, and the IκBα/NF-κB complex. Furthermore, β-carotene exhibited good potential for interactions with NF-κB essential modulator/IKK and the NF-κB complex, and α-glucan had the potential for interactions with COX-2. Therefore, supplementation with S. platensisand its bioactive compounds is expected to provide optimal benefits. Several studies have predicted the molecular interactions of the active ingredient of Spirulina platensis as an anti-inflammatory compound. However, these interaction studies did not review the modulation of the NF-κB activation pathway, which involves various factors. This study demonstrated the potential of the bioactive compounds of S. platensis for modulating immune function by reducing inflammation through the inhibition of the NF-κB activation pathway. Phycocyanobilin was predicted to have good potential for molecular docking with multisubunit IκB kinase (IKK)1/IKKA, IKK2/IKKB, NF-κB-inducing kinase, and the IκBα/NF-κB complex. Furthermore, β-carotene exhibited good potential for interactions with NF-κB essential modulator/IKK and the NF-κB complex, and α-glucan had the potential for interactions with COX-2. Therefore, supplementation with S. platensis and its bioactive compounds is expected to provide optimal benefits.